If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Hg(x) = 2g(x) Multiply gH * x gxH = 2g(x) Multiply g * x gxH = 2gx Solving gxH = 2gx Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-2gx' to each side of the equation. -2gx + gxH = 2gx + -2gx Combine like terms: 2gx + -2gx = 0 -2gx + gxH = 0 Factor out the Greatest Common Factor (GCF), 'gx'. gx(-2 + H) = 0Subproblem 1
Set the factor 'gx' equal to zero and attempt to solve: Simplifying gx = 0 Solving gx = 0 Move all terms containing g to the left, all other terms to the right. Simplifying gx = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-2 + H)' equal to zero and attempt to solve: Simplifying -2 + H = 0 Solving -2 + H = 0 Move all terms containing g to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + H = 0 + 2 Combine like terms: -2 + 2 = 0 0 + H = 0 + 2 H = 0 + 2 Combine like terms: 0 + 2 = 2 H = 2 Add '-1H' to each side of the equation. H + -1H = 2 + -1H Combine like terms: H + -1H = 0 0 = 2 + -1H Simplifying 0 = 2 + -1H The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| (5x-1)/x=1 | | -40(-28/3) | | .1(f-7)+.05f=.8 | | -(x+3)=2+7 | | log32b=-1/4 | | 42=3w-9 | | 3x+2(3)=4 | | 5-3x=-4[3(x+2)-1] | | 7d=4+6d | | 2(-14/3)-40 | | 9y+4=8y-5 | | -2v/9=-12 | | 8=y/25.6 | | .4(e+5)-.3e=17 | | (5x-1)/1=1 | | 8(4-x)=4(x+5) | | 3x-6.2=14.2 | | -8d=-9d+7 | | 30=-5/2u | | 90=(x+2)(y+1.5) | | 7f/3=5 | | m^2-10m+19=-8 | | 5X+3-X=15+X | | 4c=(a-b)/3 | | 49v^2+16=-56v | | b/3=15.2 | | 10n=7n+9 | | log(132-4x)=2 | | 54=d | | 2x+54=24 | | Cos(5x)=0.8 | | 1200m=600 |